The multicolored Asian lady beetle, Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae), a not so new invasive insect in Colombia and South America - Kondo, Takumasa; González F., Guillermo (Journal of World Insect Systematics, 2025)
The first reports of the multicolored Asian lady beetle Harmonia axyridis (Pallas, 1773) (Coleoptera: Coccinellidae) in Colombia appeared in 2011. However, based on museum insect specimens, the introduction of H. axyridis in Colombia occurred in 1989 or earlier, making it the second oldest record of the species in South America after the deliberate releases of the species in Argentina in 1986. Currently in Colombia, H. axyridis is well established and is here recorded from the States of Antioquia, Caldas, Cauca, Cundinamarca, Nariño, Tolima and Valle del Cauca.